Serum estrone concentration, estrone sulfate/estrone ratio and BMI are associated with human epidermal growth factor receptor 2 and progesterone receptor status in postmenopausal primary breast cancer patients suffering invasive ductal carcinoma - Vincze, Borbála; Kapuvári, Bence; Udvarhelyi, Nóra; Horváth, Zsolt; Mátrai, Zoltán; Czeyda-Pommersheim, Ferenc; Kőhalmy, Krisztina; Kovács, Judit; Boldizsár, Mariann; Láng, István; Kásler, Miklós (SpringerPlus, 2015)
Background We investigated in postmenopausal women with primary breast cancer prior to surgical intervention whether, serum levels of different steroid hormones and hormonal precursors associated with tumor tissue estrogen receptor (ER), progesterone receptor (PR) and human epidermal growth factor receptor 2 (HER2) status. Methods We enrolled 1,042 patients suffering invasive ductal carcinoma undergoing surgical resection in the National Institute of Oncology, Hungary between 2003 and 2011. Serum parameters were measured by RIA/IRMA assays; tumor tissue ER, PR and HER2 status was assessed histologically. Patients were classified according to tumor receptor status. Case–case analysis subjects were categorized into four subgroups based on serum hormone concentrations in ER, PR and HER2 receptor-negative cases, respectively. Results Serum estrone sulfate and dehydroepiandrosterone sulfate levels correlated with each other and also with serum estrone and estradiol levels. According to case–case study the odds ratios in the highest quartile were 1.517 (p = 0.0305, P trend = 0.0394) for androstenedione, 1.495 (p = 0.0317, P trend < 0.0105) for estrone and 0.654 (p = 0.0273, P trend < 0.0151) for estrone sulfate/estrone ratio in PR+ vs. PR− tumors. Regarding HER2 status (HER2+ vs. HER2−), the odds ratios for estrone, estrone sulfate and estrone sulfate/estrone ratio were 0.530 (p = 0.0234, P trend = 0.0595), 2.438 (p = 0.0042, P trend < 0.0066) and 3.118 (p = 0.0001, P trend < 0.0001) in the highest quartile, respectively. Of note significantly increased BMI associates with PR+ and ER +/PR+ status while significantly decreased BMI was observed in HER2+ cases. Conclusions Taken together, measurement of serum estrone and estrone sulfate concentrations prior to surgical intervention might support the individualization of regime in postmenopausal primary breast cancer patients.